The First Polish Translation of Kant’s The Contest of the Faculties in the Collections of Vilnius University Library - Kaśkiewicz, Kinga; Kupś, Tomasz (Problemos, 2018)
[full article, abstract in English; only abstract in Lithuanian] The collection of Vilnius University Library contains an incomplete, anonymous manuscript of a Polish translation of The Contest of the Faculties by Immanuel Kant. Numerous features of the manuscript (terminology, syntax and handwriting) confirm that it is a fragment of the lost translation by Józef Władysław Bychowiec, one of the most important popularisers of Immanuel Kant’s philosophy in Poland and Lithuania at the beginning of the 19th century. The manuscript is the earliest known work by Bychowiec, probably completed during his philosophical studies in Königsberg.